Cyclohexanedodecol-Assisted Interfacial Engineering for Robust and High-Performance Zinc Metal Anode - Wu, Zhenzhen; Li, Meng; Tian, Yuhui; Chen, Hao; Zhang, Shao‑Jian; Sun, Chuang; Li, Chengpeng; Kiefel, Milton; Lai, Chao; Lin, Zhan; Zhang, Shanqing (Nano-Micro Letters, 2022)
Aqueous zinc-ion batteries (AZIBs) can be one of the most promising electrochemical energy storage devices for being non-flammable, low-cost, and sustainable. However, the challenges of AZIBs, including dendrite growth, hydrogen evolution, corrosion, and passivation of zinc anode during charging and discharging processes, must be overcome to achieve high cycling performance and stability in practical applications. In this work, we utilize a dual-functional organic additive cyclohexanedodecol (CHD) to firstly establish [Zn(H2O)5(CHD)]2+ complex ion in an aqueous Zn electrolyte and secondly build a robust protection layer on the Zn surface to overcome these dilemmas. Systematic experiments and theoretical calculations are carried out to interpret the working mechanism of CHD. At a very low concentration of 0.1 mg mL−1 CHD, long-term reversible Zn plating/stripping could be achieved up to 2200 h at 2 mA cm−2, 1000 h at 5 mA cm−2, and 650 h at 10 mA cm−2 at the fixed capacity of 1 mAh cm−2. When matched with V2O5 cathode, the resultant AZIBs full cell with the CHD-modified electrolyte presents a high capacity of 175 mAh g−1 with the capacity retention of 92% after 2000 cycles under 2 A g−1. Such a performance could enable the commercialization of AZIBs for applications in grid energy storage and industrial energy storage. Highlights: 1 Cyclohexanedodecol (CHD) could facilitate the Zn dendrite-free plating/stripping at a nanoscale. 2 The CHD molecules could effectively modify the hydrated Zn(H2O)62+ structure in aqueous Zn ion batteries. 3 The addition of CHD could establish robust protection layers on the Zn electrode surface. 4 The CHD-modified electrolytes exhibit long-term cycling stability.